Functional assessment of isolated right heart failure by high resolution in-vivo cardiovascular magnetic resonance in mice. - Frydrychowicz, A; Spindler, M; Rommel, E; Ertl, G; Haase, A; Neubauer, S; Wiesmann, F (2007)
Precise and noninvasive characterization of the development of the cardiac phenotype in murine models of heart failure has been widely demanded in modern cardiovascular research. High-resolution cardiovascular magnetic resonance (CMR) has been proven to be a powerful tool for the accurate and reproducible assessment of LV and RV parameters in healthy mice. Whereas changes in LV parameters in models of heart failure have been thoroughly evaluated, RV dysfunction has not. Purpose of this study was to characterize a model of isolated RV failure induced by pulmonal banding by in vivo CMR at 7T. RV parameters differed significantly from those of normal mice in terms of RV end-diastolic volume (EDV: 85 +/- 14 microL vs. control 36 +/- 3 microL, p < 0.0001), RV end-systolic volume (ESV: 121 +/- 10 microL vs. control 84 +/- 4 microL, p < 0.005) and RV ejection fraction (EF: 31 +/- 6 % vs. control 57 +/- 2 %, p < 0.001). With regard to EDV, ESV, SV and EF LV parameters, there were no significant differences between pulmonary banded and control mice indicating overt isolated RV failure.